Nutritive values of dried pineapple pulp and some tropical grasses using invitro gas production method (2008)
The experiment was carried out to access the nutritive value of dried pineapple pulp (DPP) compared to the nutritive value of some tropical grasses using in- vitro gas production technique. The grasses were: Panicum maximum, Pennisetum purpureum, Andropogon tectorum and Cynodon dactylon.2mg of dried, ground pineapple pulp was incubated with rumen liquor, buffer solution, macro and micro mineral solutions, reducing solution and usazurin. The incubation was due at 39°Cfor 24 hours. The same procedure was due for the grasses. The amount of methane, organic matter digestibility and metabolizable energy of the samples were compared. Findings revealed that dried pineapple pulp has higher organic matter digestibility and sufficient crude fibre. Also, DPP produced higher levels of methane than other fibre sources. lt can therefore be concluded that DPP can be mixed with other feed ingredients as a supplement for ruminant production.